Design and implementation of event-triggered adaptive controller for commercial mobile robots subject to input delays and limited communications. (September 2021) - Al Issa, Sami; Kar, Indrani
Abstract: Nowadays, tracking control of mobile robots under network circumstances is a fertile topic of great research interest in control and robotics communities. In this paper, an adjustable event-triggered mechanism based on Lyapunov analysis is proposed to reduce the communication burden in the controller-to-robot channel. Besides, a compensation system is introduced to deal with input delays. Unlike other dynamic models of mobile robots that consider torques or voltages as control inputs, the derived dynamic model admits direct commands of desired linear and angular velocities which is highly desirable for commercial mobile robots available in the market. Due to the unavailability of internal parameters of the robot, an adaptive law is designed to estimate them on-line during the operation. The proposed event-triggered adaptive control scheme (ETAC) is experimentally validated on a commercial robot (PatrolBot). The obtained results are consistent with simulations and show a significant saving in bandwidth usage compared to traditional time-triggered implementation.